2013
DOI: 10.1111/cobi.12139
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit Power Analyses for Occupancy‐Based Monitoring of Wolverine in the U.S. Rocky Mountains

Abstract: Conservation scientists and resource managers often have to design monitoring programs for species that are rare or patchily distributed across large landscapes. Such programs are frequently expensive and seldom can be conducted by one entity. It is essential that a prospective power analysis be undertaken to ensure stated monitoring goals are feasible. We developed a spatially based simulation program that accounts for natural history, habitat use, and sampling scheme to investigate the power of monitoring pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 41 publications
2
82
0
Order By: Relevance
“…We emphasize the use of biological knowledge of the target species coupled with clearly defined a-priori objectives that link monitoring or research effort with defined ecological questions or conservation actions (Martin et al, 2009). Our study also illustrates the value of data simulation approaches for assessing methods and study design before embarking on empirical data collection (Zurell et al, 2010; Ellis, Ivan & Schwartz, 2013). However, it is not always feasible for practitioners to carry out their own simulation exercises.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We emphasize the use of biological knowledge of the target species coupled with clearly defined a-priori objectives that link monitoring or research effort with defined ecological questions or conservation actions (Martin et al, 2009). Our study also illustrates the value of data simulation approaches for assessing methods and study design before embarking on empirical data collection (Zurell et al, 2010; Ellis, Ivan & Schwartz, 2013). However, it is not always feasible for practitioners to carry out their own simulation exercises.…”
Section: Discussionmentioning
confidence: 85%
“…However, values of detection probability are dependent upon the length of the sampling occasion and researchers will often employ sampling occasions that are measured in weeks rather than days (Ellis, Ivan & Schwartz, 2013). Thus, if the daily detection probability is 0.03, we can recalculate p using the p * formula ( p * = 1−(1− p ) s ) such that at 1 week p = 0.19, 2 weeks = 0.35 and so on ( s is the number of sampling occasions).…”
Section: Methodsmentioning
confidence: 99%
“…This demonstration of the complexity in carnivore spatial behaviour provides a stronger foundation for science-based management of wolverine populations that are subject to strong conservation and management concerns in many parts of its distribution (Saether et al 2005;Persson et al 2009;Inman et al 2013). Our results have implications for the design and interpretation of population monitoring schemes (Ellis et al 2014;, harvest strategies (Saether et al 2005) and conflict mitigation .…”
Section: Discussionmentioning
confidence: 89%
“…Studies of presence-absence (Gaston et al 2000) and occupancy (MacKenzie and Nichols 2004, MacKenzie et al 2006, Temple and Gutie´rrez 2013 of animals have reported a positive relationship between abundance and occurrence. Further, even for large changes in population size, intensive sampling is necessary to observe changes in occupancy (Ellis et al 2014). For example, occupancy estimates will increase only if additional sites are used as population densities increases.…”
Section: Discussionmentioning
confidence: 99%